It's about time: theorizing amodern time in historical organization studies. Issue 1 (11th November 2020) - Durepos, Gabrielle; Weatherbee, Terrance; Mills, Albert J.
Abstract : Purpose: This paper features a critique of the treatment of time in modern and postmodern historical organization studies. The authors reply to the critique by drawing on Lefebvre's notion of rhythm to theorize time in an amodern condition. The purpose of this study is to call on historical organization studies scholars to theoretically engage with time. Design/methodology/approach: After a pointed literature review of the treatment of time in modern and postmodern historical organization studies, an ANTi-History approach to time is developed through an exploration of how rhythm can inform key ANTi-History facets. Findings: New insights on key ANTi-History facets are developed in relation to time. These include seeing the past as history through rhythmic actor-networks, a description of relationalism informed by situated rhythms, a suggestion that the performative aspect of history is rhythmic and an illustration of what one might see if they watched an amodern historian at work. Originality/value: Lefebvre's concept of rhythm has been largely neglected in historiography and historical organization studies. Rhythm offers a way to understand time in relation to situated actor practices as opposed to the universal clock or chronological time.